The materiality of silence The curious cases of Munari, Charlip and their picturebooks with no pictures - Campagnaro, Marnie (FronteiraZ. Revista do Programa de Estudos Pós-Graduados em Literatura e Crítica Literária, 2020)
Picturebooks are by no means a homogeneous body of texts and they require different approaches to interpret their meaning-making mechanisms. A wide variety of challenges can be offered by contemporary picturebook research. One of these challenges refers to the investigation of a singular typology of picturebooks: picturebooks with no pictures. How do these picturebooks work? What kind of reading experience do they activate in young readers? The goal of my essay is to analyse the role of white space, the morphosyntactic characteristics and the narrative mechanisms of these picturebooks. I will focus on two pictureless stories dealing with a white silent snowy landscape: Little White Riding Hood by Bruno Munari (1981) and It looks Like Snow by Remy Charlip (1957). These two authors were able to transform white, apparently empty space into novel visual narratives capable of effectively engaging children and promoting their imagination and creative thinking.